AB1094 Association between use of traditional chinese medicine and medication adherence among chinese-american rheumatology patients. (15th June 2017) - Sun, K; Tian, H; Chang, YJ; Lee, L; Leng, JC; Mandl, LA
Abstract : Background: Chinese-Americans (CA) are a fast-growing US immigrant group with high utilization of Traditional Chinese Medicine (TCM) and worse SLE and RA outcomes than Caucasians (1, 2). The effect of TCM use on adherence to prescribed western medications for systemic rheumatic diseases is unknown. Objectives: To evaluate whether TCM use is associated with adherence to western medicines prescribed for systemic rheumatic diseases among CA patients. Methods: Patients with systemic rheumatic diseases were recruited from 2 rheumatology clinics that serve a predominantly CA immigrant population. Inclusion criteria were speaking Mandarin or English and having medication(s) prescribed by the rheumatologist. TCM use, adherence, Patient-Reported Outcomes Measurement Information System (PROMIS) domains, and other variables were assessed using validated instruments available in English and Chinese. Adherence was classified as high or medium/low based on the 8-item Morisky Medication Adherence Scale (3). Medication complexity was assessed using the Medication Regimen Complexity Index (MRCI) (4); higher score indicates more complexity. Results: 177 enrolled, mean age 54 (range 20–97), 62% female, 73% ≤high school education, 75% Medicaid (subsidized insurance), and only 18% spoke English. Diagnoses were RA (43%), SLE (17%), SpA (16%), Sjogren's (8%), gout/CPPD (6%), and other (10%). 49% reported TCM use in the past year, most commonly tuina massage (48%), acupuncture (47%), and herbs (39%). 27% reported high adherence. Table 1 shows significant univariate associations with high adherence. In multivariate analysis adjusting for all variables in Table 1, only TCM use (OR 2.6, p=0.027) and higher MRCI (OR 1.1, p=0.019) were associated with high adherence. Conclusions: Among poorly integrated and low socioeconomic status CA rheumatology patients, TCM use was statistically significantly associated with high adherence to western medication, as was higher MRCI. TCM use does not appear to represent an alternate but rather complementary approach to disease management in these patients. Future studies should evaluate whether TCM use is associated with disease activity and outcomes over time. References: Barton JL, et al. Racial and ethnic disparities in disease activity and function among persons with rheumatoid arthritis from university-affiliated clinics. Arthritis Care Res 2011;63:1238–1246. Mok MY, Li WL. Do Asian patients have worse lupus? Lupus 2010;19:1384–1390. Morisky DE, et al. Predictive Validity of a Medication Adherence Measure in an Outpatient Setting. J Clin Hypertens 2008;10:348–354. George J, et al. Developmennt and Validation of the Medication Regimen Complexity Index. Ann Pharmacoepidemiol 2004;38:1369–1376. Disclosure of Interest: None declared